2016
DOI: 10.1177/1847980416663678
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism investigation for remarkable decreases in sensitivities from micron to nano nitroamine

Abstract: Raw hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) was pulverized to nano RDX by mechanical milling, and their micron morphology and surface elements were probed by transmission electron microscope and X-ray photoelectron spectroscopy analyses. Thermal analysis was employed to take a kinetic evaluation on thermal decomposition of raw and nano RDX. The result indicated that activation energy for thermal decomposition of nano RDX is closed to the value of raw RDX, which means nano RDX had similar thermal reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…15 Wang et al have reduced the particle size of RDX successfully from 87 μm to 270 nm by the milling method and analyzed the factors affecting the safety of explosives by combining Khasanov’s and Merzhanov’s models to establish the relationship between the mean particle size, critical temperature, and critical size of hot spots. 16 They concluded that the mean particle size does not affect sensitivity, unless the mean particle size is lower than 400 nm. Their study also revealed that nanoscale level materials had lower sensitivity than the raw materials because of the small hot-spot size and high critical hot-spot temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Wang et al have reduced the particle size of RDX successfully from 87 μm to 270 nm by the milling method and analyzed the factors affecting the safety of explosives by combining Khasanov’s and Merzhanov’s models to establish the relationship between the mean particle size, critical temperature, and critical size of hot spots. 16 They concluded that the mean particle size does not affect sensitivity, unless the mean particle size is lower than 400 nm. Their study also revealed that nanoscale level materials had lower sensitivity than the raw materials because of the small hot-spot size and high critical hot-spot temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Their study also revealed that nanoscale level materials had lower sensitivity than the raw materials because of the small hot-spot size and high critical hot-spot temperature. 16 Guo et al prepared CL20 nanoparticles with a particle size of 200 nm by utilizing ball-milling technology. 17 Liu et al used bidirectional grinding mill technology to convert micron-sized particles of RDX, HMX, and CL-20 to nanosized particles.…”
Section: Introductionmentioning
confidence: 99%
“…According to current research in this eld, nanocrystallization and cocrystallization are superior to surface coating and spheroidization in terms of the enhancement of the insensitivity of energetic materials. [3][4][5] In our previous studies, using mechanical milling, we fabricated many kinds of nanoexplosives and investigated their properties. [6][7][8][9] These nanoexplosives were of particle sizes of 100-200 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The compatibility problem of multiple components in composite energetic materials can be solved by coating the surface of the particles. This process isolates individual components to improve their stability, reduce toxicity, and extend their warranty period [2–4]. Thus, the preparation of the core‐shell structure of microcapsules has become an important research direction in the field of nitramine energetic materials.…”
Section: Introductionmentioning
confidence: 99%